Voces silenciadas: Discursos alrededor del suicidio en población Trans Masculina y No-Binaria (2024)
The research aimed to explore the discursive experience of trans masculine and non-binary individuals regarding suicide, based on their lived experiences, using a critical social approach with qualitative methodology, phenomenological design, and exploratorydescriptive scope. A group of 4 trans masculine and non-binary individuals from Colombia and Mexico was selected through non-probabilistic convenience sampling with specific inclusion criteria. A focus group with open-ended, non-directive interviews was utilized, followed by content analysis to understand how discourses on suicide are constructed within this population.